(3OjhGf GdJdYaQjs - (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s ((3YHOGddg Hf gGOj s)
(3ChdgG (B:s
(3hef cdGe GdJdYaQj(B: (3de CRd oecKQkG Ydjg GdSDGdG hLhGHG eG YfOg dj Shi dG s
(3BNQgG (B:s
(3eG cGf CNUH CQVge dh CfgG JSbj EPG XeFJ SLGFH COeYj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B43 - (3U(B68s
(3fSNI QGHYIs
(3hbO SbWJ GdUaMGJ (B47(3, (B48(3, (B61(3, (B62s
(3YHGQI Yf oeNJGQGJ ef OjhGf GdJdYaQj Vef eNJGQGJ TYQjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs